STRENGTHENING FINANCIAL GOVERNANCE AND ACCOUNTING-BASED BUSINESS STRATEGIES TO ENHANCE THE COMPETITIVENESS OF TRADITIONAL MARKET TRADERS IN SUBANG JAYA (SS15) - Basrowi Basrowi; Juhari Ali; Rahemee Rahemee; Mohd Mizan bin Asalam; Bambang Dwi Suseno; Gema Ika Sari; Nani Rohaeni; Riani Puasarin; Hidayatullah Hidayatullah; Nining Sulastri Kurnia; Fitriyansyah Fitriyansyah (Yayasan Education and Social Center, 2026)
This community service program aimed to strengthen financial governance and accounting-based business strategies to enhance the competitiveness of traditional market traders in Subang Jaya (SS15), Malaysia. The program adopted a participatory and empowerment-based approach involving 25 traditional market traders from various small-scale business sectors. The implementation consisted of several stages, including needs assessment, training, mentoring, and evaluation. Data were collected using quantitative and qualitative methods through questionnaires, interviews, observations, and documentation. The effectiveness of the program was evaluated using pre-test and post-test analysis combined with thematic analysis. The results indicate significant improvements in financial governance, accounting practices, and strategic business capabilities among participants. Prior to the program, most traders demonstrated weak financial governance, including the absence of budgeting and poor separation between personal and business finances. After the intervention, the proportion of participants categorized as having good financial governance increased from 16% to 56%. In terms of accounting practices, participants showed substantial progress in recording transactions and preparing simple financial reports, with full implementation increasing from 16% to 60%. Furthermore, the ability of traders to formulate accounting-based business strategies improved significantly, as reflected in the increase of participants with high strategic capability from 16% to 52%.